Simulation Interventions for the Classroom to Support the Acquisition of Interprofessional Competencies - Gamble, Brenda J (Cureus, 2021)
Interprofessional collaboration (IPC) supports the delivery of quality and safe healthcare. The acquisition of interprofessional competencies both pre-licensure and post-licensure are key to implementing this approach in the healthcare workplace. This report documents the development and implementation of a simulation intervention to support interprofessional education (IPE) in the undergraduate classroom for pre-licensure learners. The learning activity framework includes an exposure phase (e.g., didactic classroom instruction) and an immersion phase (e.g., simulation intervention and debriefing). Details on the debriefing process are included as it is key to achieving the learning objectives. The three learning activity pilot tests (n=150) revealed that learners recognized that interprofessional competencies were an important asset to support IPC. The pilot tests identified the need for further development in order for students to make a connection with the mastery phase (i.e., clinical placement). The next steps will include the development and incorporation of formative tools to assess learners’ progress, as well as a plan to evaluate the learning activity that will connect all three phases (exposure, immersion, and mastery) of the learning framework.